Primary synchronous small and non-small cell lung cancer in the same lung lobe: A case report - Dzian, Anton; Ivan, Fúcˇela; Zdenko, Hut’ka; Peter, Szépe (Monaldi Archives for Chest Disease, 2017)
Synchronous multiple primary lung cancer (SMPLC) means tumours present at the same time, which are separate and have different histology. We present the case of a 66-year-old patient with a combination of small-cell lung carcinoma (SCLC) with adenocarcinoma in the same lobe with metastasis of SCLC in the mediastinal lymph node. This is aÂ rare case. We performed a standard left upper video-assisted thoracoscopic lobectomy with mediastinal lymphadenectomy and adjuvant therapy targeted to SCLC was administered. Despite advances in imaging methods and diagnostic procedures in pneumology a diagnosis of SMPLC is often discovered only intraoperatively or accidentally during the histological examination. Actually, no guidelines exist for the treatment protocol of such cases. Multiple methods of management of SMPLC, mainly complete anatomical resection with lymphadenectomy combined with chemotherapy or radiotherapy should be adopted according to the histologic types, staging and molecular testing of the tumours. These rare cases of SMPLC require individual treatment and multidisciplinary approach.Â 